"I" value justice, but "we" value relationships: Self‐construal effects on post‐transgression consumer forgiveness. Issue 2 (12th June 2015) - Sinha, Jayati; Lu, Fang‐Chi
Abstract: Causal attributions and brand‐relationships are known to determine how consumers react to brand transgressions. Considering both transgression controllability and brand‐relationship strength, the authors show that self‐construal moderates consumer reactions to brand transgressions. Three studies using different product and service failure scenarios demonstrate that consumers who have independent self‐construals are more forgiving when the brand has no control over the transgression, regardless of brand‐relationship strength. However, consumers who have interdependent self‐construals are more forgiving when they have strong relationships with the transgressing brand, even if the brand is at fault. Furthermore, the salience of justice concerns versus expectancies for long‐term brand‐relationships underlies the self‐construal effects on consumer forgiveness.